Electric vehicle charging process and parking guidance app - Alface, G. (2019)
This research work presents an information system to handle the problem of real-time guidance towards free charging slot in a city using past date and prediction and collaborative algorithmssincethereisnoreal-timesystemavailabletoprovideinformationifachargingspotisfree or occupied. We explore the prediction approach using past data correlated with weather conditions. This approach will help the driver in the daily use of his electric vehicle, minimizing the problem of range anxiety, provide guidance towards charging spots with a probability value of being available forcharginginacontextfortheappandsmartcities. Thisworkhandlestheuncertaintyofthedrivers togetasuitableandvacantplaceatachargingstationbecausemissingreal-timeinformationfromthe systemandalsoduringthedrivingprocesstowardsthefreechargingspotcanbetaken. Weintroduce a framework to allow collaboration and prediction process using past related data.